Communication Networks as Base for Mobility – Trend Development of Network Architectures - Keil, Reiner; Krone, Dirk; Kremenova, Iveta; Madlenak, Radovan (Communications - Scientific letters of the University of Zilina, 2015)
New network architectures are required for a flexible service provisioning. These are characterized by the transition from channel-switching to packet-switched networks. The amount of the collected information needs to be provided in these network architectures at the right time at the right place for processing in the control systems and end-systems. The warranty of parameters such as duration and availability within the network architectures is a requirement for the function of the service to be provided. The requirements must be specified for an application to a suitability of the architecture in terms of safety with the required parameters for reliability and specifically to evaluate the high availability.